Effect of two different blood purification modes on vascular endothelial function - TONG Fang; HE Hui-qing; HU Da-jun (Linchuang shenzangbing zazhi)
Objective To investigate the effect of routine hemodialysis and long-term hemodialysis combined with perfusion on vascular endothelial function in patients with maintenance hemodialysis. Methods Patients with maintenance hemodialysis in Yichang second people’s hospital were divided into two groups. One group was treated with hemodialysis alone(HD group),and the other group was treated with hemodialysis through blood perfusion(HD + HP group). Each patient was tested once a month for routine blood test, electrolytes and renal function before and after hemodialysis. We used the formula to calculate the spKt/V every month. We measured the blood flowmediated vasodilation of brachial artery(FMD) and blood flow rate( △Q%) every three months.The effects of two different blood purification modes on vascular endothelial function were compared.Results The damage degree of vascular endothelial function in HD + HP group was significantly lower than that in HD group. There was no significant difference in dialysis adequacy between the two groups. The incidence of cardiovascular and cerebrovascular adverse events was significantly reduced in HD + HP group. Compared with before treatment, the hemoglobin level of patients in the HD + HP group increased significantly after treatment( P < 0. 05), and the blood pressure decreased significantly( P < 0. 05). There was no difference in hemoglobin before and after treatment in HD group( P > 0.05). Conclusions The treatment of hemoperfusion combined with hemodialysis can delay vascular endothelial function damage in patients with maintenance hemodialysis, improve renal anemia,lower blood pressure, and reduce cardiovascular and cerebrovascular adverse events.